Al-Ni-Co-Si 준결정 코팅층의 미끄럼 마찰과 마모특성에 미치는 온도 및 용사방법의 영향 - 김재수; 김유찬; Eric Fleury; 김도향; 김원태; 안효석; 이상목 (대한금속·재료학회, 2002)
Powders of Al-Ni-Co-Si alloys were produced by gas-atomization under protective N₂ atmosphere. The gas-atomized powders were sieved to select them having a size range of -200∼+400 mesh. Quasicrystalline coatings were deposited onto the 304 stainless steel substrates using two thermal spraying techniques: high velocity oxygen fuel(HVOF) and air plasma spraying(APS). The friction and wear behaviors of the coatings were evaluated under the various conditions. The wear amount of both the coating and the chromium coated cast iron disc during the testing was determined by measuring the weight loss after the test. Analysis of the wear debris and of the wear track on both the coating and Cr coated cast iron disk was observed by using scanning electron microscopy. Friction coefficient of the plasma coating was about 0.36 and of the HVOF coating was about 0.43. The APS-deposited coatings, which had a higher level of porosity, exhibited a higher friction coefficient and lower wear resistance than the HVOF processed coatings. However, as the temperature during wear testing increased, the wear resistance of APS was improved and tended to be similar to that of HVOF coatings. Higher wear resistance of HVOF was attributed to the densification of the coating sub-surface with lower porosity and agglomeration of shall wear debris into large cylindrical particles and foramtion of intermediate layer.